2008
DOI: 10.1021/ma801678h
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyridine-Based Poly(ether sulfones) and their Study in High Temperature PEM Fuel Cells

Abstract: Novel pyridine-based aromatic copolymers containing 4,4′-biphenol or hydroquinone groups in the main chain were synthesized and characterized as polymer electrolytes for proton exchange membrane fuel cells (PEMFCs). Depending on the copolymer composition and pyridine monomer content in most cases soluble and high molecular weight copolymers were obtained. Flexible membrane films were prepared by casting N,Ndimethylacetamide (DMA C ) solutions of copolymers. 1 H NMR and size exclusion chromatography were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 38 publications
3
40
1
Order By: Relevance
“…As is presented in this work, see Figure 8, in the case of copolymer II, conductivity values slightly increase as its doping level increases from 80 to 270 wt.-%. Comparing with our previous work [26], copolymers with more linear structure (bearing sulfone groups instead of phosphinoxide) show slightly better conductivity. A factor that seems to be of interest is the introduction of aliphatic side groups like methyl groups in the tetramethyl biphenol monomer used in the case of copolymer I.…”
contrasting
confidence: 69%
See 2 more Smart Citations
“…As is presented in this work, see Figure 8, in the case of copolymer II, conductivity values slightly increase as its doping level increases from 80 to 270 wt.-%. Comparing with our previous work [26], copolymers with more linear structure (bearing sulfone groups instead of phosphinoxide) show slightly better conductivity. A factor that seems to be of interest is the introduction of aliphatic side groups like methyl groups in the tetramethyl biphenol monomer used in the case of copolymer I.…”
contrasting
confidence: 69%
“…TGA measurements of copolymer I doped at levels ranging between 150 and 200% showed that, probably due to a plasticisation that takes place upon acid doping, at temperatures above 130°C the material starts to exhibit a viscoelastic behaviour while retaining its mechanical integrity. This phenomenon does not reflect to materials that bear the sulfone group instead of the phosphinoxide one, as clearly shown in our previous work [25][26][27]. Furthermore, a difference in the chain conformation or the phase separation in the presence of phosphoric acid could result to this differentiation in the behaviour of the copolymers studied in this work in comparison to previously studied copolymers.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…Therefore, the membranes are imbibed in the highly concentrated H 3 PO 4 solution for high H 3 PO 4 loading. In previous H 3 PO 4 -doped PBI studies, 11 to 14 M solutions are always employed as the optimal concentrations of H 3 PO 4 solutions, [28][29][30][31] However, the results shown in Fig. 3 are in apparent disagreement with this empirical rule of thumb.…”
Section: Hydrated Conductivitymentioning
confidence: 93%
“…Pyridine based membranes such as Advent Technologies TPS membrane have also been investigated for HT-PEMFC applications [10][11][12][13][14][15][16]. These membranes exhibit glass transition temperatures of~270 …”
Section: High Temperature Polymer Electrolyte Membranesmentioning
confidence: 99%